Assessment of quality of life in patients with end stage renal failure using KDQOL-SF - Zahid Nadeem; Abdul Bashir; Abdul Qadeer; Mirwais Khan (Archives of Renal Diseases and Management - Peertechz Publications, 2021)
Background: Chronic Renal Failure (CRF) is a general health problem having a genuine effect on the quality of life of the patients experiencing hemodialysis. Objectives: The aim and objectives of this cross-sectional study was to evaluate the effect of dialysis on the quality of life of patients with End Stage Renal Failure (ESRF). Methodology: Sample of 103 Patients Undergoing hemodialysis were included in study from two hospitals (public sector) of Quetta Pakistan. Information was gathered by the fruition of a self-utilized survey a part of KDQOL-SF fusing the instrument of the SF-36 survey of health and an extra poll so as to incorporate demographics. Writing survey depended on studies, audits and articles got from global information bases concerning the quality of life of individuals with end stage renal failure. Result: A total of 103 responses were collected out of which 54 (53.4%) were males and 49 (47.6%) were females with the mean age between 30 and 45 (38.8%) years old. Majority of the patients were in a Moderate state of health 56 (54.4 %) and 33(32%) were those who had Bad health state, while 14 (13.6%) patients with Good quality of health. Majority of the patients were not at all bothered by dryness of skin (27.2%), itchy skin (39.8%), lack of appetite (32%), washed out or exhausted (39%), soreness of muscles (35%), pain in their joints (32%), easy brouising (45.6%), sleepiness at the day time (42.7%), cramps during dialysis (60.2%) and after dialysis (36.9%), stiffness of joints (33%), back pain (31.1%), numbness in hands or feet (37.9%), bone aches (30.1%), muscle pain (41.7%), headache (26.2%), stomach problem or nausea (31.1%), shortness of breath (43.7%), faintness or dizziness (64.1%), hot or cold spells (36.9%), trouble concentration (52.4%), trouble in getting breath (52.4%), blurred vision (42.7%), chest pain (52.4%), swelled ankles (34%), loss of tast 3 (35.9%), clotting or other access site problems (62.1%) and majority of the patients were extremely bothered by lack of strength (36.9%), weakness and fatigue (51.5%), excessive thirst (41.7%), dryness of mouth (34%), trouble in sleeping (37.9%), head ach (26.2%). Majority of the patients were somewhat bothered by high blood pressure (19.4%) and low blood pressure (13.6%). Conclusion: Specific variables, such as age, gender, social support, income, the quality of life of the patients is effected either negatively or positively by education physical functioning health and disease symptoms. Particular factors, for example, age, gender, social support, income, education, physical working wellbeing and ailment side effects can influence either decidedly or adversely the quality of patients life.